2014
DOI: 10.1073/pnas.1412901111
|View full text |Cite
|
Sign up to set email alerts
|

Disassembly of mitotic checkpoint complexes by the joint action of the AAA-ATPase TRIP13 and p31 comet

Abstract: Significance The mitotic checkpoint system has an important role to ensure accurate segregation of chromosomes in mitosis. This system regulates the activity of the ubiquitin ligase Anaphase-Promoting Complex/Cyclosome (APC/C) by the formation of a negatively acting Mitotic Checkpoint Complex (MCC). When the checkpoint is satisfied, MCC is disassembled, but the mechanisms of MCC disassembly are not well understood. We show here that the ATP-hydrolyzing enzyme Thyroid Receptor Interacting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
131
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(141 citation statements)
references
References 30 publications
(67 reference statements)
5
131
0
Order By: Relevance
“…These results clearly demonstrate that maintenance of the SAC is critical to prevent cancer formation. TRIP13 has been shown to promote the dissociation of the MCC complex (15)(16)(17), which subsequently inactivates the SAC to prevent the completion of mitosis (18). Thus, overexpression of TRIP13 and silencing of MCC components have similar effects on cells, since both can lead to dysregulation of the SAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results clearly demonstrate that maintenance of the SAC is critical to prevent cancer formation. TRIP13 has been shown to promote the dissociation of the MCC complex (15)(16)(17), which subsequently inactivates the SAC to prevent the completion of mitosis (18). Thus, overexpression of TRIP13 and silencing of MCC components have similar effects on cells, since both can lead to dysregulation of the SAC.…”
Section: Discussionmentioning
confidence: 99%
“…TRIP13 forms a stable hexameric ring, and ATP binding, as well as ATP hydrolysis, are critical for the function of the protein (13). Previous studies have revealed that TRIP13 is a novel component of the spindle assembly checkpoint (SAC) pathway (14)(15)(16)(17), which is crucial for the accurate distribution of duplicated chromosomes (18). Defects in the SAC pathway induce failure in chromosome separation and result in aneuploidy, which eventually leads to cellular apoptosis or transformation (19).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TRIP13 and p31 comet promoted the inactivation of the mitotic checkpoint (30). However, the function of SAC-related proteins in mitosis has not yet been tested in plants, and several SAC proteins have been found to be involved in plant meiosis, such as MPS1, Aurora kinases, AtPCH2, and CDC20.1 in Arabidopsis, as well as CRC1 and BRK1 in rice (12,37).…”
Section: Discussionmentioning
confidence: 99%
“…The crystal structure of Mad2-p31 comet dimer was analyzed, and p31 comet was considered to mimic the structure of Mad2 to inhibit the dimerization of Mad2, allowing the metaphase/anaphase transition during mitotic checkpoint inactivation (29). Recent studies have shown that TRIP13 links p31 comet to disassemble the mitotic checkpoint complex (MCC) (30,31).…”
Section: Significancementioning
confidence: 99%
“…But recent attention has focused on mutual inhibition between the MCC and the APC/C (Reddy et al 2007), which requires a particular APC/C subunit, APC15 (Mansfeld et al 2011;Foster and Morgan 2012;Uzunova et al 2012). In animal cells, a second important player for MCC disassembly is the p31 comet protein (Habu et al 2002;Teichner et al 2011;Westhorpe et al 2011), which has recently been implicated in targeting an AAA ATPase to the MCC to initiate its disassembly (Eytan et al 2014;Wang et al 2014).…”
Section: The Biochemistry Of Mitosismentioning
confidence: 99%